Key stage and model of hydrocarbon accumulation of Ordovician reservoir in Gucheng area, Tarim Basin, China - Zhang, You; Li, Qiang; Niu, Yongbin; Li, Bin; Shi, Yanqing; Pang, Yumao (Frontiers in Earth Science, 2023)
The previously obtained understanding of the reef flat reservoir and dolomite reservoir for a long time supports the hydrocarbon exploration of the Lower Paleozoic carbonate reservoir in the Tarim Basin. However, the exploration practice is facing challenges of high heterogeneity of deep carbonate reservoirs and oil and gas reservoir destruction in local areas. This research presents a case study of the Ordovician in the Gucheng area, Tarim Basin. Based on the cores, thin sections, cathode luminescence tests, laser ablation U-Pb isotope geochronometry, bitumen reflectance, and fluid inclusion tests of 18 wells of the Ordovician of the study area, seismic interpretation, and the regional understandings, key stage and model of hydrocarbon accumulation of Ordovician reservoir in Gucheng area are systematically investigated. Our research shows that: (1) The Tarim Basin mainly develops three sets of effective source rocks, namely the Cambrian Yuertusi Formation, Cambrian Moheershan Formation, and Mid-Lower Ordovician Heituwa Formation, which are concentrated in the slope-basin facies of eastern Tarim Basin. (2) The Gucheng area is located in a favorable paleo-structural position. The pathway system composed of vertical faults and lateral unconformities occurs in the paleo-uplift, which is critical for hydrocarbon migration and accumulation. (3) The laser in-situ U-Pb dating, distribution and genesis of reservoir bitumen, burial-thermal maturation history, and the homogenization temperature of fluid inclusions suggest that the multi-stage tectonic thermal events of the Caledonian and Hercynian stages result in key adjustment and modification to deep hydrocarbon accumulation. Due to magmatic hydrothermal activities, the Caledonian primary oil reservoir massively evolved into oil-cracking gas reservoirs and residual paleo-oil reservoirs. (4) The paleo tectonic-fluid effect plays an important factor controlling the development of the Ordovician reservoirs. The evolution of the hydrocarbon accumulation in Gucheng area can be divided into three stages, namely formation of primary oil and gas reservoirs, oil-cracking gas reservoirs, and adjustment, destruction and reforming of gas reservoirs. To sum up, the western and northern parts of the paleo-uplift with favorable source-reservoir-cap rock assemblage and less effects of hydrothermal activities are the favorable zones for hydrocarbon exploration in the Gucheng area, the Tarim Basin.